The Epistemology of Media Literacy Paradigm from the Perspective of Postmodern Philosophy - الصادق رابح (International Journal of Social Communication, 2023)
This research paper investigates the current paradigm of media literacy from a postmodern epistemological assumptions’ perspective. It focuses on the current state of media literacy and argues that it reveals a crisis in the current paradigm of this concept that its comprehensive features have not yet been revealed. The paper argues that the knowledge and skills that are highly valued in the traditional paradigm of media literacy need to be contextualized in the postmodern perspective. Thomas Kuhn's approach to scientific revolutions is used here to investigate the development paths of media literacy as a concept, as a field of study, and as a practical practice. However, the paper does not overlook the current contexts that are characterized by the predominance of the post-truth era. This concept is present in media and other academic and nonacademic writings, as the most prominent manifestation of postmodernism, where the idea of truth is relativist.